Warisan Pendidikan Islam Nusantara: Suatu Perubahan dan Keberlangsungan - Djaelani Haluty (Al-Ulum, 2016)
Islamic Nusantara gives a great contribution to Indonesia by bequeathing the various of Islamic educational institutions, which until now still exist and sustainably, Islamic Nusantara has a treasury of educational institutions such a comprehensive, innovative and integrative. However, the great contribution of Islamic Nusantara with the educational institution where its educates and liberates the mankind from ignorance and the backwardness its not necessarily got appreciated for its efforts, but the existence was a "blasphemed" by people who identify themselves as a transnational movement. Islamic Nusantara is called as Islam which has a great relation between local tradition and culture, this article wish to discribing the seed of islamic Nusantara in Indonesia as well as integration of Islamic scholarship and Western.